(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how local governments utilise regional dialects and languages in television and film to strengthen local identity and trust within the context of public health communication. Drawing on case studies from Guangdong and Hebei provinces, the research finds that adapting public health messages to local dialects significantly improves communication effectiveness. In Guangdong, the local government tailored COVID-19 vaccination messages to the Cantonese dialect, leading to a 28% higher vaccination rate compared to the national average and a stronger emotional connection, with 72% of respondents finding the messages more relatable. In contrast, Hebei relied on standardised national messaging without local adaptation, resulting in poor audience comprehension and unmet communication benchmarks. The study concludes that in a linguistically diverse country like China, the use of regional dialects in public health communication is essential for cultural governance and building public trust. It recommends greater attention to linguistic adaptation to improve the reach and impact of health campaigns.